![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: m>n
=>2m>2n
=>2m-2>2n-2
b: m>n
=>-3m<-3n
=>-3m+1<-3n+1
c: m>n
=>2m>2n
=>2m+3>2n+3
mà 2n+3>2n+1
nên 2m+3>2n+1
d: m>n
=>-5m<-5n
=>-5m+3<-5n+3
mà -5n+3<-5n+7
nên -5m+3<-5n+7
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Rút gọn A = ( 5 m ) 2 = 25 m 2 . Với m = 2 Þ A = 100.
b) Rút gọn B = -12x + 26. Với x = 10 Þ B = -94.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{2m^2+3m+1}{2m^2-m-1}=\frac{2m^2+2m+m+1}{2m^2-2m+m-1}\)
\(=\frac{2m\left(m+1\right)+\left(m+1\right)}{2m\left(m-1\right)+\left(m-1\right)}=\frac{\left(m+1\right)\left(2m+1\right)}{\left(m-1\right)\left(2m+1\right)}\)
\(=\frac{m+1}{m-1}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=24x^{2m-1+3-2m}y^{6-3m}-\dfrac{24}{7}y^{3n-7+6-3n}\cdot x^{3-2m}+8x^{3-2m+2m}\cdot y^{6-3n+3m}-24x^{3-2m}y^{6-2n+2}\)
\(=24x^2y^{6-3m}-\dfrac{24}{7}x^{3-2m}\cdot y^{-1}+8x^3y^{-3n+3m+6}-24x^{3-2m}y^{-2n+8}\)
b: \(=2x^{2n+1-2n}-6x^{2n+2-2n}+3x^{2n-1+1-2n}-9x^{2n-1+2-2n}\)
\(=2x-6x^2+3-9x\)
\(=-6x^2-7x+3\)
\(2m\left(5m-3\right)+\left(2m-3\right)\left(3m-1\right)\)
\(=10m^2+4m+6m^2-2m-9m+3\)
\(=16m^2-7m+3\)
Trả lời...................
Easy.....................
2m (5m-3) + ( 2m - 3 ) (3m-1)
=10m^2+4m+6m^2-2m-9m+3
=16m^2-7m+3
..........................học tốt..........................